HISTOPATHOLOGICAL SPECTRUM OF THYROID LESIONS AND ITS CORRELATION WITH BIOCHEMICAL AND RADIOLOGICAL FINDINGS-STUDY 100 CASES - SUKHPAL KAUR; NINDER KUMAR; HARPAL SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study was to study the correlation of histopathological findings of thyroid lesions and establish its correlation with biochemical and radiological findings. Methods: The present study was a prospective study conducted in the Department of Pathology, Government Medical College and Rajindra Hospital Patiala, Punjab. 100 cases were included in the present study. Results: Out of 100 cases studied, 87 cases were euthyroid, 8 were hypothyroid, and 5 were hyperthyroid. On USG, 50 thyroid lesions were mixed echoic, 26 were isoechoic, 10 were hyperechoic, and 14 were hypoechoic. Majority of hypoechoic lesions were diagnosed as malignant histopathologically. Conclusion: Histopathology is gold standard. Combined opinion on the nature of a thyroid lesion should be done based on clinical findings, ultrasound findings.